2018
DOI: 10.1590/1678-992x-2016-0321
|View full text |Cite
|
Sign up to set email alerts
|

Ractopamine supplementation improves leanness and carcass yield, minimally affecting pork quality in immunocastrated pigs

Abstract: This study was carried out to determine the combining effects of feeding up to 15 mg kg -1 ractopamine (RAC) to physically castrated (PC) pigs or those injected with an anti-GnRF vaccine (IC), on growth performance during suckling, weaning, growing and finishing phases. Out of a total of 1,160 male piglets, 50 % were surgically castrated at age 7, while 50 % underwent immunization against GnRF on the 103 rd and 136 th day of life. A completely randomized design, with two treatments (PC and IC), was used from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Both compounds, FA and ractopamine, showed an anabolic effect. It is well documented that β-AA ractopamine improves several productive and carcass parameters [ 29 , 30 ]. ADG and feed conversion are the most important production parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Both compounds, FA and ractopamine, showed an anabolic effect. It is well documented that β-AA ractopamine improves several productive and carcass parameters [ 29 , 30 ]. ADG and feed conversion are the most important production parameters.…”
Section: Discussionmentioning
confidence: 99%
“…However, the absence of season effects in the present study may be explained by the low cortisol levels which evidently reflected good environmental and pre-slaughter handling conditions. Since pigs have limited abilities to heat loss, they are essentially susceptible to heat stress (Ingrain 1965;Adejumo and Egbunike 1988), which can explain the higher lactate concentrations found in pigs during summer (Dalla Costa et al 2018). In the literature, the effects of fasting interval on cortisol levels are contradictory.…”
Section: Physiological Stress Indicatorsmentioning
confidence: 99%
“…Another common practice used in swine production to improve growth performance and the percentage of lean meat in the carcasses without altering the meat quality is the supplementation with ractopamine hydrochloride (RAC). RAC is a β-adrenergic agonist used as growth-promoting in swine finishing diets that acts as a repartitioning agent, reducing adipose tissue nutrients and redirecting them to muscle protein synthesis (Almeida et al, 2012;Athayde et al, 2012;Costa et al, 2018). Several studies demonstrated that both immune castration and RAC supplementation add value to the swine meat and carcass (Athayde et al, 2012;Lowe et al, 2014;Rocha et al, 2014;Costa et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…RAC is a β-adrenergic agonist used as growth-promoting in swine finishing diets that acts as a repartitioning agent, reducing adipose tissue nutrients and redirecting them to muscle protein synthesis (Almeida et al, 2012;Athayde et al, 2012;Costa et al, 2018). Several studies demonstrated that both immune castration and RAC supplementation add value to the swine meat and carcass (Athayde et al, 2012;Lowe et al, 2014;Rocha et al, 2014;Costa et al, 2018). Rocha et al (2014) demonstrated that immune castrated males (IC) receiving 7.5 mg/kg of RAC exhibited leaner carcasses compared to surgically castrated (SC) with or without RAC inclusion in the diet, maintaining pork quality and good welfare indicators.…”
Section: Introductionmentioning
confidence: 99%